ANALYZING OHANIAN’S SOURCE CREDIBILITY MODEL ON 4 YOUTUBE MUSICIANS - Fahrezi, Muhamad Ariel; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract.Social media is the biggest marketing media today. One of the biggest social media today is YouTube and one of the biggest category in YouTube is music, and the content creators are called YouTube musicians. YouTube musicians are content creators who make videos with their musical performance. With publishing themselves through YouTube, they can get noticed and eventually, get famous. But this doesnâ??t affect everyone on YouTube because some videos become viral, the other videos may be overshadowed by it. With this phenomenon, many other newcomers want to try to become famous by doing the same thing, but theyâ??re confused about their strategy to make the videos to effectively gain views. So, the goal of this research is to analyze the content strategy of four YouTubers using qualitative content analysis from four YouTube musicians, two of them have more subscribers from the other two. The result of the study shows that â??attractivenessâ?? is very important for making music video content. The impact of this study will help new YouTube musicians to form a better strategy for making their videos.Keywords: music, social media, video content strategy, YouTube, YouTube Musicians